Emotional intelligence and schizophrenia spectrum disorders: a critical review - Martins,Fernanda de Marzio Pestana (2019)
Abstract Introduction Emotional intelligence (EI) is a theoretical construct postulated by Mayer and Salovey to designate the ability to perceive, understand, use and manage emotions. The study of EI in schizophrenia offers new insights into the disorder’s cognitive and functional impacts. Objectives To comprehensively review studies analyzing EI impairment in schizophrenia spectrum disorders using standardized instruments. Methods Searches were run on MEDLINE/PubMed, Google Scholar, Cochrane, LILACS, Embase, ClinicalTrials.gov and SciELO databases. The only validated instrument used was the Multifactor Emotional Intelligence Scale (MSCEIT). Articles that used all branches of the MSCEIT to assess EI in schizophrenia spectrum disorders and healthy controls were included in the review. Results We found 30 articles on this topic. The studies analyzed showed a significant impairment of MSCEIT total score in patients with schizophrenia spectrum disorders when compared to healthy controls. In relation to the MSCEIT branches, understanding of emotions and management of emotions are the most impaired branches. Conclusion Since most studies are cross-sectional, it is not possible to establish a cause and effect relationship between EI deficits and schizophrenia spectrum disorders. Therefore, longitudinal studies are needed to establish a clearer relationship between these variables. By so doing, we may be able to intervene for prevention and management of these disorders, aiming at better quality of life for patients.